Factors associated with medication adherence in patients living with cirrhosis. Issue 1 (January 2016) - Polis, Suzanne; Zang, Ling; Mainali, Bhawana; Pons, Rachel; Pavendranathan, Gokulan; Zekry, Amany; Fernandez, Ritin
Abstract : Aims and objectives: Medication adherence in people with cirrhosis is largely unknown. This study aims to determine adherence patterns and factors associated with adherence in patients with cirrhosis. Background: Prescribed medications are a pivotal component in the clinical management of cirrhosis with potential to retard disease progression and reduce complication risks. Medication adherence is necessary to optimise health outcomes. Understanding why medications are missed may help to develop strategies and inform nursing practice. Design: Prospective cohort study. Methods: Participants ( n = 29) diagnosed with cirrhosis attending a tertiary hospital consented to complete a self‐reported survey. Demographic information, adherence to medications, patient knowledge and quality of life data were collected, collated, checked and analysed usingspss version 21. Results: Less than half of the 28 patients who completed the adherence questionnaire ( n = 13, 46%) reported that they had never missed medication. Being forgetful, being away from home and falling asleep contributed to nonadherence. Having less abdominal symptoms, less fatigue and increased emotional well‐being were significantly associated with patients never missing medications. Conclusions: To our knowledge this is the first published study to describe adherent behaviour and the reasons medications are missed in this population. The percentage of nonadherent participants is of concern considering the potential morbidity risk that is associated with missed medications and rebound symptoms of cirrhosis. Strategies to improve and sustain adherence levels are required including enhanced adherence counselling offered to patients who are deteriorating or experience periodic exacerbation of symptoms. Relevance to clinical practice: Study findings have the potential to change clinical practice especially the way nurses target motivational adherence counselling, key treatment messages, education and adherence monitoring. The results presented here provide a basis for developing adherence strategies and nursing management plans to improve adherence and health outcomes in people with cirrhosis.